Bitter taste perception in Neanderthals through the analysis of the TAS2R38 gene - Lalueza-Fox, Carles (The Royal Society, 2009)
The bitter taste perception (associated with the ability or inability to taste phenylthiocarbamide) is mediated by the TAS2R38 gene. Most of the variation in this gene is explained by three common amino-acid polymorphisms at positions 49 (encoding proline or alanine), 262 (alanine or valine) and 296 (valine or isoleucine) that determine two common isoforms: proline–alanine–valine (PAV) and alanine–valine–isoleucine (AVI). PAV is the major taster haplotype (heterozygote and homozygote) and AVI is the major non-taster haplotype (homozygote). Amino acid 49 has the major effect on the distinction between tasters and non-tasters of all three variants. The sense of bitter taste protects us from ingesting toxic substances, present in some vegetables, that can affect the thyroid when ingested in large quantities. Balancing selection has been used to explain the current high non-taster frequency, by maintaining divergent TAS2R38 alleles in humans. We have amplified and sequenced the TAS2R38 amino acid 49 in the virtually uncontaminated Neanderthal sample of El Sidrón 1253 and have determined that it was heterozygous. Thus, this Neanderthal was a taster individual, although probably slightly less than a PAV homozygote. This indicates that variation in bitter taste perception pre-dates the divergence of the lineages leading to Neanderthals and modern humans.